Implementation of Law Number 24 of 2007 in Disaster Management of the Mount Merapi Eruption - Rahma Auliya; Agus Setio Widodo (Diplomasi : Jurnal Demokrasi, Pemerintahan dan Pemberdayaan Masyarakat, 2026)
This study examines how Law Number 24 of 2007 concerning Disaster Management was implemented in the Special Region of Yogyakarta during the Mount Merapi eruption. The focus of this study is to determine the extent to which the legal framework can promote effective, coordinated, and sustainable disaster management in areas prone to volcanic hazards. The research indicates that, particularly in terms of institutional frameworks, early warning systems, coordination between stakeholders such as the Regional Disaster Management Agency (BPBD), the Center for Volcanology and Geological Hazard Mitigation (PVMBG), and community participation in the Disaster Resilient Village program, the law's implementation has been relatively good. However, the study also identified several issues that hinder optimal implementation. These include a lack of community preparedness, policy inconsistencies across administrative regions, and limited institutional resources at the regional level. The results suggest that cross-regional coordination should be strengthened, standard operating procedures should be updated based on empirical experience, and disaster literacy should be improved through ongoing education and simulations. Consequently, this research contributes to the development of a more sustainable, flexible, and inclusive volcanic disaster management policy in Indonesia.